2021
DOI: 10.1371/journal.pone.0250453
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential metabolic biomarkers of rectal cancer and of the effect of neoadjuvant radiochemotherapy

Abstract: We report a pilot study on the feasibility of determinations of circulating levels of paraoxonase-1 (PON1) and compounds related to energy metabolism as biomarkers for the evaluation of patients with rectal cancer (RC), and the effects produced by neoadjuvant radiochemotherapy (NRCT). We studied 32 patients treated with radiotherapy plus capecitabine concomitant chemotherapy and 48 control subjects. We identified pre-NRCT PON1 and α-ketoglutarate as the parameters that best discriminated between RC patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 65 publications
2
21
0
Order By: Relevance
“…On the other hand, among DEP upregulated in exosomes of good responders was PON1, an important antioxidant enzyme, which elevated serum level was previously observed in rectal cancer patients in response to neoadjuvant radiochemotherapy [ 15 ]. Interestingly, signal transduction proteins S100A8 and S100A9 upregulated in exosomes of poor responders were previously proposed as CRC tumor-specific exosomal markers, involved in migration, leucocyte recruitment, tumor-promoting inflammation, and formation of premetastatic niches [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, among DEP upregulated in exosomes of good responders was PON1, an important antioxidant enzyme, which elevated serum level was previously observed in rectal cancer patients in response to neoadjuvant radiochemotherapy [ 15 ]. Interestingly, signal transduction proteins S100A8 and S100A9 upregulated in exosomes of poor responders were previously proposed as CRC tumor-specific exosomal markers, involved in migration, leucocyte recruitment, tumor-promoting inflammation, and formation of premetastatic niches [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on the role of exosomes in response to radiation and RT concern changes in transcriptome and proteome, yet much less is known about the metabolome component of these vesicles [ 43 ]. In general, only a few studies addressed RT-induced changes in metabolic profiles of rectal cancer [ 14 , 15 , 44 ], and there is no data about the potential of small molecules to discriminate patients who responded differently to radiotherapy. Here, we observed that metabolites present in exosomes and plasma had some potential to discriminate patients with different responses to neo-RT, and a few differentially accumulated metabolites (DAMs) were observed in both specimens (though DEPs detected in exosomes were much more numerous).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Principal Component Analysis (PCA) was calculated using the factoExtra (v1.0.7) 60 and factoMineR (v2.4) 61 . To examine the correlation of DNA methylation and regulation of gene expression, the Spearman’s rank correlation coefficient was calculated between the scaled M-values 62 and normalized expression values for the 1,186 CpG-sites and corresponding genes using ggcorr function in GGally package in R 63 . Heatmaps were generated using ComplexHeatmap package (v 4.0.3).…”
Section: Methodsmentioning
confidence: 99%